Experimental Analysis of Vapour Absorption Generator integrated with Thermal Energy Storage system. (2019) - Ponshanmugakumar, A.; Rajavel, R.
Abstract: A vapour absorption Air-conditioning system can run replacing the compressor by a pump, absorber and a generator. The generator can be operated by the low thermal energy like solar, exhaust heat of IC engines etc. But all the period this heat energy will not be available. In this present research the generator part alone considered for experiment. A new model of generator heater is designed and fabricated. The heat transfer capacity and the thermal energy charging and discharging were calculated for analysis. The suitable capacity of generator is integrated with Phase change material is designed to operate a vapour absorption system in the capacity of 3.5 KW. The generator design is modified for Phase change material containment. The average temperature of the heat energy available will be around 60°C to 80°C. In this temperature range suitable Phase change material is selected for thermal energy storage tank. The experiment is conducted on this storage tank for thermal energy charging and discharging by varying the material composition.